2012
DOI: 10.1111/j.1476-5381.2012.01912.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of targeting hydrogen peroxide metabolism in the treatment of brain ischaemia

Abstract: For many years after its discovery, hydrogen peroxide (H2O2) was viewed as a toxic molecule to human tissues; however, in light of recent findings, it is being recognized as an ubiquitous endogenous molecule of life as its biological role has been better elucidated. Indeed, increasing evidence suggests that H2O2 may act as a second messenger with a pro-survival role in several physiological processes. In addition, our group has recently demonstrated neuroprotective effects of H2O2 on in vitro and in vivo ischa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 130 publications
(173 reference statements)
3
43
0
Order By: Relevance
“…MDA production during free radical attack on membrane lipoproteins and polyunsaturated fatty acids is an indicator of lipid peroxidation. SOD, an antioxidant enzymes and super oxygen free radical scavenger, is critical to clean the superoxide anion into hydrogen peroxide and water [36,37]. Our study has demonstrated that the notable increase in MDA in the IR group confirmed the oxidative damage in the skeletal muscle, and the marked decrease in SOD levels showed the exhaustion of antioxidant enzymatic activity.…”
Section: Discussionsupporting
confidence: 53%
“…MDA production during free radical attack on membrane lipoproteins and polyunsaturated fatty acids is an indicator of lipid peroxidation. SOD, an antioxidant enzymes and super oxygen free radical scavenger, is critical to clean the superoxide anion into hydrogen peroxide and water [36,37]. Our study has demonstrated that the notable increase in MDA in the IR group confirmed the oxidative damage in the skeletal muscle, and the marked decrease in SOD levels showed the exhaustion of antioxidant enzymatic activity.…”
Section: Discussionsupporting
confidence: 53%
“…42 However, the biological role of ROS has recently been better elucidated, and ROS have been recognized as ubiquitous endogenous signaling molecules. 43 Moderate increase of ROS was shown to act as a molecular signal exerting downstream effects that ultimately induce endogenous defense mechanisms, culminating in enhanced stress resistance and increased life span. 44 Specific targets for a balanced ROS regulation are peroxisomeproliferator-activated receptors (PPARs).…”
Section: Discussionmentioning
confidence: 99%
“…The second question is connected to the first and concerns the context in which the redox control of MGL activity might be operational. Dysfunctional redox states such as brain ischemia are associated with rises in the levels of H 2 O 2 and other reactive oxygen species (Armogida et al, 2012). In those conditions, MGL sulfenylation might act as an intrinsic neuroprotective mechanism by potentiating 2-AG signaling at CB 1 receptors.…”
Section: Significancementioning
confidence: 99%